The use of feeding plate to improve weight gain in infants with cleft palate during surgical preparation: a case report - Hidayatullah, Hidayatullah; Pertiwi, Arlette Suzy Puspa; Husyaerry, Machmud Al (Universitas Padjadjaran, 2025)
Introduction: Cleft palate impairs feeding ability in infants, leading to nutritional deficiencies and delayed surgical intervention. Early management is critical to optimize growth parameters. This case report aims to evaluate the use of a feeding plate in an infant with cleft palate, focusing on its impact on nutrition and surgical preparation. Case Report: An 18-day-old female infant with a Veau II cleft palate presented with feeding difficulties. A feeding plate was fabricated using an elastomeric impression technique. After six weeks of plate use, the infant’s weight increased from 3.3 kg to 4.6 kg, and feeding efficiency improved markedly without nasal regurgitation. Conclusion: The application of a feeding plate significantly improved nutritional outcomes and enhanced surgical readiness in an infant with cleft palate.